ALIGNMENT TYPOLOGY IN ENGLISH AND UZBEK: A COMPARATIVE STUDY OF SYNTACTIC ROLES AND CASE MARKING (PROBLEMS AND SOLUTIONS OF SCIENTIFIC AND INNOVATIVE RESEARCH, 2025)
This article examines how English and Uzbek distribute syntactic roles and mark grammatical relations through their alignment systems. Although both languages follow a nominative–accusative pattern, they diverge significantly in the way these relations are encoded. English relies mainly on fixed word order and a limited case paradigm, while Uzbek expresses grammatical roles through an extensive case-marking system and flexible syntactic structure. By comparing subject and object behavior, case patterns, and argument alignment, this study highlights typological distinctions that help explain the deeper structural logic of each language. The findings show that English tends toward analytic alignment strategies, whereas Uzbek demonstrates agglutinative and morphologically explicit alignment. These observations contribute to cross-linguistic typology and provide insights for translation studies and language pedagogy.